NATURAL CHARACTERISTICS’ IMPACT ON URBAN ENVIRONMENTAL QUALITY: A CASE STUDY OF AIN BEIDA CITY, ALGERIA - Nassira Guemini; Foued Benghadbane (International Journal of Innovative Technologies in Social Science, 2024)
The city of Ain Beida struggles with a complex interplay of natural and technical characteristics that significantly influence its urban development, environmental quality, and overall sustainability. The city’s natural components present both opportunities and challenges for urban planning and development. This paper explores the impacts of these factors on urban development and environmental quality. Additionally, it delves into the consequences of natural characteristics on urban development policies, addressing the dilemma between preserving green spaces and the imperative for urban expansion. Artificial obstacles pose challenges to urban expansion and impact security, as well as overall environmental health. Furthermore, the paper discusses the risks associated with natural and technological elements emphasising the importance of safety measures and emergency response protocols. The urban development policies of Ain Beida have undergone a shift primarily driven by limited land availability. Urban densification, aimed at optimizing land use, has been adopted, but it comes with environmental trade-offs. Considering the challenges and opportunities identified, the paper concludes with a set of recommendations.